ANALISIS PENGGUNAAN KALIMAT IMPERATIF DALAM DOA KATOLIK - Adhani, Agnes (Widya Warta, 2016)
The aim of this study is to describe formal forms, marker characteristics, and meanings of imperative sentences used in Catholic prayer. The research  made use of descriptive qualitative method. The data were analyzed using the following techniques:  (1) paraphrasing, (2) deletion, (3) substitution, (4) expansion, and (5) permutation. The results indicated that (1) the formal forms consist of (a) transitive active imperatives (117 in number), (b) intransitive active imperatives (37 in number), and (c) passive imperatives (4 in number), (2) the  imperative sentences are characteristized by four markers, namely (a) the absence of functional subject  (120 in number),  (b) the usage of particle -lah (109 in number), (c) prefix deletion (92 in number), and (d) the inversion of order, placing verbs at the beginning of sentences, and (3) there are five kinds of meaning of imperative sentences, namely (a) polite command (104 in number), (b) invitation (34 in number), (c) request (14 in number), (d) prohibition/negative command (5 in number), and (e) common order/command (1 in number).